Serum creatinine- and cystatin C-based indices are associated with the risk of subsequent sarcopenia: evidence from the China Health and Retirement Longitudinal Study - Ning, Xin; Xie, Chao; Kong, Yaozhong (Frontiers in Nutrition, 2024)
Background: Serum creatinine (Cr)-and cystatin C (CysC)-based indices have been suggested as alternative markers for sarcopenia, but their predictive value for sarcopenia risk is uncertain, which was investigated in the present study in the Chinese population with the middle and older ages.Methods: Data from the China Health and Retirement Longitudinal Study (CHARLS) were collected in the 2011 and 2015 waves. All participants were free of sarcopenia at the baseline. Sarcopenia was diagnosed when low muscle mass and grip strength or low physical performance were present. Four indices were computed: predictive skeletal muscle mass index (pSMI), total-body muscle mass (TBMM), creatinine-to-cystatin C ratio (CCR), and sarcopenia index (SI). Restricted cubic splines and logistic regression models were used to assess the effects of these indices on sarcopenia risk.Results: Among 4527 participants without sarcopenia at the baseline ( 2011), the median age was 58 yearold (IQR: 52-65), with 52.7% women. Followed up in year 2015, The incidence of sarcopenia was 20.8 per 1000 person-years (376 / 4527). Neither CCR nor SI showed linear or nonlinear associations with the risk of subsequent sarcopenia. However, a decrease in pSMI and TBMM was significantly associated with an increased risk of sarcopenia [adjusted per-SD decrease OR, 2.93; 95% CI, 2.09-4.13, P < 0.001; adjusted per-SD decrease OR: 2.38, 95% CI: 1.80-3.16, P < 0.001, respectively].Conclusions: In the middle and older age of Chinese population, decreased pSMI and TBMM were associated with an increased risk of subsequent sarcopenia, whereas CCR and SI showed no such correlation. Thus, pSMI and TBMM may serve as potential biological indicators for predicting the risk of sarcopenia, and decreased pSMI and TBMM may be the early biomarkers for diagnosis and intervention of sarcopenia.